Genetic Authentication of Acacia Senegal (L.) Wild - Evilla Olabiyi Badiru; Ibrahim Nasiru; Ernest C. Ajaegbu; Anita Oketa (International Journal of Genetic Modifications and Recombinations, 2024)
A study was carried out to ascertain the taxonomic identity and phylogenetic lineage of three presumed Acacia senegalensis using molecular markers. Three (3) varieties of seeds presumed to belong to Acacia spp. were collected from the Rubber Research Institute of Nigeria (RRIN) Benin City and three BP haplotypes (A, B, and C) was used as control for the analysis. These seeds were processed at the Applied Biotech International Laboratory Nigeria in January 2018 for molecular identification and analysis. Genomic DNA was carefully extracted from the harvested embryos of the 6 seed samples by standard mechanical crushing in sterile tubes, cell harvest and enzymatic lysis, followed by chemical purification, using Mo Bio Power Soil DNA Isolation kit. The intergenic spacer of partial CPLST gene was amplified using the cplst gene primers at 250bp. The nucleotide sequences generated from the 3 samples were then blasted against the sequences in the gene Bank using the NCBI Blast tool to identify the nucleotide sequences like the Acacia samples and the sequences were analyzed on CLUSTAL W 2.0 multiple sequence alignment. From the blast result for sample A, 5 hits were generated, 3 out of the 5 hits had 46% query cover and 81% identity to the nucleotide sequence of sample A. This gives a clue that sample A could be Acacia senegal. sample B was blasted against the nucleotide sequences in the gene bank; only one isolate had nucleotide sequence like sample B with 18% query cover and 86% identity. This led to the assumption that sample B could be Canjanus cajan isolate. Sample C had a nucleotide sequence like that of Acacia estrophiolata with 63% query cover and 78% identity. The phylogenetic analysis of the sequences from the 3 Samples (A, B, C) showed that sample A appeared to be more closely related to Acacia senegal isolate being that it evolved from the same ancestors. Sample A is identified as Acacia senegal (Also now referred to as Senegalia senegal) with a high confidence and E –value.
Keywords: Nucleotide sequences; gum Arabic; intergenic spacer of partial CPLST gene; phylogenetic analysis